IMPROVING THE MANAGERIAL QUALITY OF THE HEAD OF MADRASAH IN THE MADRASAH FRIENDS PROGRAM IN BREBES-INDONESIA - Gozali, Imam; Fajarin, Fajarin; Fatimah, Siti; Suklani, Suklani (IJBLE Scientific Publications Community Inc., 2023)
In the current context, the managerial quality of madrasah is still uneven. Therefore, it is important to equalize the managerial quality of madrasas. This study describes the efforts of the Regional Office of the Ministry of Religion of Central Java in improving the managerial quality of madrasa heads through the madrasa companion program. This study uses a descriptive qualitative method, relying on primary data and extensive literature studies. Primary data sources were obtained through interviews with madrasa principals, teachers, school committees in public and private madrasas and secondary data were collected from relevant documents and similar studies. The results of this study indicate that the madrasa companion program in the form of mutual assistance and a spirit of sharing between advanced and underdeveloped madrasas has a positive impact on the progress and development of madrasas in Brebes Regency, Central Java, Indonesia.